Correlation between microbial communities changes and physicochemical indexes of Dazu Dongcai during different fermentation periods - ZHANG,Ling (2022)
Abstract Bacteria play the most important role in the fermentation process of Dongcai. At present, the flora in the fermentation process of Dazu Dongcai have not been detected. The physicochemical indexes association with microbiota changes during fermentation have not yet been evaluated. Therefore, it is necessary to explored the correlations between microbial communities and physicochemical indexes during Dazu Dongcai fermentation. Dazu Dongcai samples including five time points were prepared for four year during the spontaneous fermentation process. Microbial community dynamics and associated biochemical changes were characterized using metagenomics sequencing technology and physiochemical properties determination to identify associations between microorganisms and fermentation characteristics. These results indicated that Staphylococcus, Lactobacillus, Terrisporobacter, Blautia, Romboutsia, Bifidobacterium and Streptococcus dominated the whole fermentation process, which were strongly correlated with the physical and chemical indexes. These flora have promoting function during fermentation and may affect the quality of Dongcai. This study provides new detailed insights into the succession of microbial communities and their potential roles in Dazu Dongcai fermentation, so as to establish a correlation analysis model of key factors in the pickling process of Dazu Dongcai, which can lay a foundation for the standardized production of Dazu Dongcai.